Electrical energy conservation and its application to a sheet glassindustry - Khan, A.Z. (1996)
Electrical energy is the most common and widely used type of energy in the world. The subject of energy conservation is a concern for most energy users particularly industry. Energy conservation (ECON) becomes even more important for the third world, developing countries, where the rising energy costs and the use of efficient energy apparatus are of significant concern to both the industry and the utility. In this paper, the application of the ECON techniques by which electrical energy can be saved and made cost efficient from the industrial perspective are presented for a sheet-glass industry in a developing country (Pakistan-Asia). The selection, in particular, of a sheet-glass industry was done because electrical energy constitutes only a small amount of the overall energy used. A complete energy conservation guideline is recommended. The load profile and its overall improvement in light of these recommendations is also illustrated along with the proposed utilization of the techniques and their applications. Electrical energy management (EEM) approach for motors, PF, and tariff control is outlined and the emphasis on energy conservation technology has been elaborated. More findings of the application of energy conservation techniques of high significance are presented in the paper